An Investigation into the Challenges Facing Administration of STEM Education in Gwagwalada Universal Basic Education Junior Secondary Schools in FCT, Nigeria - Jacob, Ogunode Niyi (International Journal of Research in STEM Education, 2020)
This study aimed to investigate the challenges facing the administration of STEM Education in Gwgwalada junior secondary schools of FCT, Nigeria. The study employed a descriptive survey design. The instruments used for data collection were questionnaires titled:' Challenges facing Administration of STEM Education QuestionnaireÃ¢â‚¬Â (CFASEQ).The sample for the study comprised of 200 teachers. A simple random sampling method was used to select the sample. One hypothesis and three research instruments were used for the study. Test and retest were employed to determine the reliability of the instrument. Simple percentages were employed to analyze the data collected and a chi-square test was used to test the hypothesis. The study revealed that challenges are facing the administrations of STEM Education in Gwagwalada junior secondary schools and these challenges include; inadequate infrastructural facilities, shortage of science teachers, lack of instructional materials, lack of motivation, inadequate fund, poor supervision, high population, poor capacity development program for science teachers and negative attitude of students towards STEM education. The result also revealed that100% of the respondents agreed that the implications of the challenge facing the administration of STEM Education are responsible for poor implementation of STEM education in Gwagwalada junior secondary schools of FCT, Nigeria. From the finding, it was recommended that the government increase the funding of education and give more priority to STEM Education.